Manajemen Pengelolaan Sampah oleh Dinas Lingkungan Hidup - Yeni Saputri; M. Fachri Adnan; Zikri Alhadi (Journal of Education on Social Science (JESS), 2019)
The purpose of this study is to explain the management of waste management by the Environmental Service of Dumai City, Riau Province. This research is a qualitative research using descriptive method. The data in this study were obtained by observation, interviews, and documentation studies. The validity of the data in this study is the source triangulation technique. Based on the results of research and discussion found that management functions have not been fulfilled optimally. This is caused by the lack of budget, facilities and infrastructure such as waste equipment that is lacking and has long been so that it cannot transport so much amount of waste, the effective and efficient implementation of HR management of the Environmental Service, and the lack of socialization to the community making it difficult to carry out tasks and the participation of the community and industry players who are still low to participate in waste management activities.